Optimizing the Management of Facilities and Infrastructure in the Implementation of the Merdeka Curriculum - Whibawa, Intan Tresna; Neneng Sulastri (Shibyan: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The implementation of the Merdeka Curriculum requires adequate facilities and infrastructure. The dominance of conventional learning methods and limited facilities are the main obstacles. This study aims to analyze effective facility management models that support the Merdeka Curriculum at Sekolah Cerdas Muthahari Bandung. Method: Using a qualitative approach with case studies, this study involved the school principal, educators, and educational staff. Data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis was conducted inductively. Results: Facility management at this school is carried out systematically through four stages: participatory planning, strategic procurement, organized use, and collective maintenance. This model has proven effective in creating a conducive learning environment, improving student comfort, and facilitating innovative learning methods. Conclusion: Optimal facility management is a crucial factor for the success of the Merdeka Curriculum. An integrated management approach that involves all components of the school ensures that facilities are used efficiently and sustainably, supporting more flexible and student-centered educational goals.